Mobile Seamless Learning to Mitigate Negative Effects in Gamification of Learning - Qolbi, Muhammad Syifa'ul; Soepriyanto , Yerry; Ulfa, Saida (Universitas Pendidikan Ganesha, 2024)
Low student engagement in learning and the potential negative impacts of gamification in education are significant challenges in developing innovative learning media. This study aims to develop Mobile Seamless Learning that effectively integrates gamification elements to enhance student engagement while minimizing potential drawbacks. The research employed a development research design using the Alessi & Trollip model, which includes three main phases: planning, design, and development. The study participants consisted of 121 students from an educational technology program, selected to evaluate the application's effectiveness. Data were collected using questionnaires, and analyses were conducted using both qualitative and quantitative descriptive approaches to assess user perceptions and feedback. The findings indicate that the application received positive perceptions from students, particularly in terms of usability, ease of use, and learning experience. User feedback highlighted the application’s benefits in improving accessibility, tracking learning performance, motivating students, and supporting seamless cross-device learning. Furthermore, the application successfully created engaging and effective learning experiences, focusing on mitigating risks associated with excessive gamification elements. The study concludes that the developed Mobile Seamless Learning not only enhances student engagement but also adds value by supporting continuous learning processes, making it a suitable and innovative technology-based learning medium in the digital era.